Quality of teachers in technical higher education institutions in India. Issue 4 (10th October 2018) - Sharma, Payal; Pandher, Jagwinder Singh
Abstract : Purpose: The quality of education depends upon the quality of teachers, i.e. professional competence. The purpose of this paper is to empirically identify the state of faculty's quality in technical higher education institutions of Punjab (India) in terms of their competences. Later, differences in the quality of the faculty of both public (government funded) and private (partially or not funded by government) technical institutions were examined. Design/methodology/approach: In total, 35 technical institutes were selected to conduct a field survey and total 594 respondents including teachers, students and administrators had responded to the present study from different departments of engineering and management. The state of faculty's quality in terms of their competences has been examined through confirmatory factor analysis in AMOS 20.0. Discriminant analysis in SPSS 20.0 has been performed to find the differences in faculty of both the public and private sectors. Findings: This paper provides a broader picture of the poor quality of teachers in technical institutions of Punjab (India) in terms of lacking most of the competencies. The study also reveals significant differences in the faculty of both public and private sector institutes in terms of select competences. Originality/value: This paper demonstrates an alarming stage of poor-quality state of teachers. Therefore, educational administrators and policy makers need to show their concern for the improvement of teachers' quality in technical higher education institutions of Punjab (India).